Expression in Escherichia coli, purification and kinetic characterization of LAPLm, a Leishmania major M17-aminopeptidase - Aguado, Mirtha Elisa; González-Matos, Maikel; Izquierdo, Maikel; Quintana, Juan; Field, Mark C; González-Bacerio, Jorge (Protein expression and purification, 2021)
The Leishmania major leucyl-aminopeptidase (LAPLm), a member of the M17 family of proteases, is a potential drug target for treatment of leishmaniasis. To better characterize enzyme properties, recombinant LAPLm (rLAPLm) was expressed in Escherichia coli. A LAPLm gene was designed, codon-optimized for expression in E. coli, synthesized and cloned into the pET-15b vector. Production of rLAPLm in E. coli Lemo21(DE3), induced for 4 h at 37 °C with 400 μM IPTG and 250 μM l-rhamnose, yielded insoluble enzyme with a low proportion of soluble and active protein, only detected by an anti-His antibody-based western-blot. rLAPLm was purified in a single step by immobilized metal ion affinity chromatography. rLAPLm was obtained with a purity of ~10% and a volumetric yield of 2.5 mg per liter, sufficient for further characterization. The aminopeptidase exhibits optimal activity at pH 7.0 and a substrate preference for Leu-p-nitroanilide (appKM = 30 μM, appkcat = 14.7 s-1). Optimal temperature is 50 °C, and the enzyme is insensitive to 4 mM Co2+, Mg2+, Ca2+ and Ba2+. However, rLAPLm was activated by Zn2+, Mn2+ and Cd2+ but is insensitive towards the protease inhibitors PMSF, TLCK, E-64 and pepstatin A, being inhibited by EDTA and bestatin. Bestatin is a potent, non-competitive inhibitor of the enzyme with a Ki value of 994 nM. We suggest that rLAPLm is a suitable target for inhibitor identification.
Keywords: kinetika; rekombinantní proteiny; IMAC; Escherichia coli; Kinetic characterization; Leishmania major; pET-15b vector; Aminopeptidases; Protozoan Proteins; Expression in E. coli; Leucyl aminopeptidases; protozoální proteiny; aminopeptidasy; Recombinant Proteins; Kinetics